O ensino híbrido em cursos de licenciatura da UFMT : entendimentos e práticas pedagógicas em questão - Maia, Mirtes Dâmares Santos de Almeida (2021)
This research is linked to the Post-Graduation Program in Education (PPGE) of the Federal University of Mato Grosso (UFMT); it is part of the research line 'School Organization, Training and Pedagogical Practices', within the sphere of work of the research group 'Laboratory of Studies on Information and Communication Technologies in Education' (LêTECE). Based on the context of a digital culture and pedagogical practices supported by the use of Information and Communication Technologies (ICT), the aim of this work is to investigate which practices and strategies with the use of ICT have been adopted in licentiate degree courses, in view of the understandings of teachers and students about the blended learning. We point out that it is a research with a qualitative approach, which follows descriptive-exploratory objectives, whose theoretical reference is based on authors who discuss technologies in education, teacher training, pedagogical practices in the context of digital culture and blended learning. The research took place at UFMT, and professors and students of 13 (thirteen) licentiate degree courses were considered the participants. The data are configured based on a set composed of documentary analysis, applied on-line questionnaires, and conducted semi-structured interviews; all of which is treated following the content analysis techniques. From the results, we infer different understandings about blended learning (BL) by the participants, but the data point out that the BL is understood at UFMT, mostly, as the combination of the face-to-face education and the distance education (DE), with the use of a virtual learning environment. But even those teachers and students who understand BL from another perspective, they come together with the majority when they point out the inclusion of ICT in practices as one of the main elements for the constitution of a blended learning. Regarding pedagogical practices and BL strategies, although most teachers and students have stated their occurrence at UFMT, the data indicate that most of them are not configured as a characteristic of a blended learning, since they occur through a restrictive and limited use of some technological resources. Only a few and punctual strategies could be confirmed as being of a blended learning, what calls attention to an emergence of practices that are allied with a more critical and conscious perspective regarding the use of ICT in training, being this considered as a movement to accompany the practices of the digital culture.